Combined interpretation of geophysical, hydrogeochemical and environmental isotope data in a distal lobe of the Maros fluvial fan, Hungary – A novel approach in aquifer characterisation - Teodóra Szőcs; Ágnes Rotár Szalkai; Levente Magyar; László Palcsu; Márton Bujdosó; János Stickel; Zoltán Püspöki (Journal of Hydrology: Regional Studies)
Study region: Pannonian Basin, Hungary, Maros fluvial fan. Study focus: This paper presents a novel approach to characterise a distal lobe of a fluvial fan, demonstrating how a combined interpretation of high-resolution geophysical methods like electrical resistivity tomography and geophysical cone penetration tests together with log-correlation, hydrogeochemical, isotope and noble gas data provides a sound basis for aquifer characterisation. This multidisciplinary investigative approach is applicable to any fluvial fan to support water management. New hydrological insights for the region: (1) The studied fluvial fan forms a hydraulically interconnected aquifer system, with three channel belts and six hydrostratigraphic units. (2) Mean groundwater residence times are distinct in the aquifers studied. Holocene infiltration, with apparent residence time younger than 20–22 years is characteristic in the uppermost channel belt and forms part of local groundwater flow systems. The deeper aquifers host groundwater infiltrated during the Pleistocene, as part of the intermediate flow system. (3) Where the silty-clayey floodplain sediments have been replaced by sandy deposits, and groundwater abstraction is present, groundwater can communicate between the upper and lower channel belts, therefore fresh infiltration passes into the deeper channel belts, resulting mostly in mean residence times younger than 100 years. However, Pleistocene infiltration was detected at about 30 m below surface in the second channel belt, where the unconfined aquifer is missing and silty-clayey sediments are on the surface.